Dampak Penggunaan Anotasi Penamaan yang Berbeda pada Kinerja NER - I Made Widi Arsa Ari Saputra; I Wayan Supriana (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
In developing the NER model, naming annotations are used as an important part of the training process. The impact of using different naming annotations on NER performance has been a concern in the research community. So, the writer wants to once again, test the impact of using different naming annotations using the spaCy library on English documents. Using 2 naming schemes namely BIO and IOBES, using the spaCy model to get 0.96 accuracy for BIO and 0.95 for IOBES.